Decreased use of active coping styles contributes to elevated allostatic load index in first-episode psychosis. (October 2018) - Misiak, Błażej; Kotowicz, Kamila; Loska, Olga; Stramecki, Filip; Beszłej, Jan Aleksander; Samochowiec, Jerzy; Jabłoński, Marcin; Podwalski, Piotr; Waszczuk, Katarzyna; Wroński, Michał; Michalczyk, Anna; Sagan, Leszek; et al.
Highlights: The allostatic load index is increased in first-episode psychosis. Patients with early psychosis are less likely to use active coping styles. Lower odds of using active coping might be related to allostatic load in psychosis. Depression might mediate the effect of coping styles on allostatic load. Abstract: Accumulating evidence indicates that stress plays an important role in the development of psychotic disorders. Recent studies have revealed that patients with first-episode psychosis (FEP) present systemic biological dysregulations related to stress-exposure in terms of elevated allostatic load (AL) index. However, the mechanisms underlying this observation remain unknown. Therefore, in this study we aimed to investigate the AL index with respect to stress coping strategies in 36 FEP patients and 31 matched controls. We found significantly higher AL index in FEP patients compared to controls after co-varying for potential confounding factors. Patients with FEP were less likely to use active and task-focused coping. Lower odds of using these coping styles, planning as well as positive reinterpretation and growth were related to higher AL index in FEP patients, but not in controls. Depressive symptoms were associated with lower likelihood of using task-focused coping as well as positive reinterpretation and growth. Additionally, depressive symptoms were related to higher AL index. Finally, depressive symptoms mediated the effects of task-focused coping as well as positive reinterpretation and growth on the AL index. Our results confirm systemic biological dysregulation indexed as AL in FEP patients. Lower odds of using active coping styles might contribute to higher AL index via the mediating effect of depressive symptoms in patients with FEP. Longitudinal studies are required to establish causal inferences between coping styles, depressive symptoms and the AL index in early psychosis.